N. A. SHAIKENOV IN THE HISTORY OF STATEHOOD OF KAZAKHSTAN - Birjanova, Культай Сулейменовна (Scientific and legal journal «Bulletin of the Institute of Legislation and Legal Information of the Republic of Kazakhstan», 2022)
The article is devoted to the personality of N.A. Shaikenov as a statesman, scientist, teacher, a person who made a huge contribution to the transformation of legal education in the country. A well-educated and brilliant speaker, indomitable in his belief in the power of law expressed in the constitutions and laws of the Republic of Kazakhstan, had a significant impact on political and socio-economic reforms in Kazakhstan. As a legal theorist, he paid considerable attention to the problems of distinguishing law and the law, in order to prevent totalitarian ideas about the essence of law, the priority of the state over law in the new conditions. The practical necessity for this distinction was that in reality there is no coincidence of the due and the existent. The dialectical connection between the law and the essence of law will be continuous, as he believed, only in a state governed by the rule of law, where going beyond one's own freedom is associated with the responsibility of observing the boundaries of one's right and not violating the legal freedom of others.